Sobre o direito de ser normal: identidades normalizadas e a construção das políticas públicas de saúde para gays e lésbicas na cidade de São Paulo - Nardelli, Rachel D’Amico [UNESP] (2014)
During the 1980s the world sees a new disease appears, reached the peripheral sexualities, especially gay men, speeches and populated pictures fears and new medical terms: Kaposi's sarcoma, Grid, disease 5H, gay cancer. All these were ways to designate what in 1983 was known as the Human Immunodeficiency Virus (HIV), which causes Acquired Immunodeficiency Syndrome (AIDS). Bringing a sexual panic with the need to manage this disease, AIDS was able to articulate throughout its 30 years the device of sexuality and power devices and medical know-silent and very effective of Biopolitics. The biopolitics or biopower, to Michel Foucault's exactly the way it managed the life Pest epidemics, pandemics, these are terms that designate diseases that must be contained, they afflict large-scale population, undermining the economic relationship, with the decrease of active subjects, in addition to producing a large burden for the state with treatments. The discourses regarding AIDS have this normalizing character, double danger, blood and sex, articulated this device that tries to manage life through surveillance, rule and regulation of the body. In Brazil, these technologies were centras in gay bodies, in a historical moment in which these identities emerging homosexuality had his life crossed by AIDS, interestingly, this is exactly what has initiated the process of searching for visibility and democratic rights in the movement known as lgbt.